2010
DOI: 10.1021/bm100490s
|View full text |Cite
|
Sign up to set email alerts
|

Fast Preparation Procedure for Large, Flat Cellulose and Cellulose/Inorganic Nanopaper Structures

Abstract: Nanostructured materials are difficult to prepare rapidly and as large structures. The present study is thus significant because a rapid preparation procedure for large, flat, smooth, and optically transparent cellulose nanopaper structures is developed using a semiautomatic sheet former. Cellulose/inorganic hybrid nanopaper is also produced. The preparation procedure is compared with other approaches, and the nanopaper structures are tested in uniaxial tensile tests. Optical transparency and high tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
309
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(329 citation statements)
references
References 30 publications
16
309
4
Order By: Relevance
“…In addition to the barrier properties and related functional capabilities of nanocellulose-based layers, much research has focused on desirable attributes such as transparency Petersson and Oksman 2006;Nordqvist et al 2007;Shimazaki et al 2007;Ayuk et al 2009;Fernandes et al 2009Fernandes et al , 2010Fukuzumi et al 2009;Kim et al 2009;Nogi et al 2009;Petersson et al 2009;Sehaqui et al 2010;Hassan et al 2011;Pereda et al 2011Pereda et al , 2014Stevanic et al 2011;Yang et al 2011;Aulin et al 2012;Hu et al 2013;Li et al 2013a;Tome et al 2013;Khan et al 2014b;Kumar et al 2014;Kurihara and Isogai 2014;Tammelin and Vartiainen 2014;Ambrosio-Martin et al 2015b;Honorato et al 2015;Oun and Rhim 2015;Toivonen et al 2015a,b). Hu et al (2013) showed that nanocellulose films could be rendered conductive by deposition of tindoped indium oxide, while still retaining their transparency; solar cells prepared with such films were successfully demonstrated.…”
Section: Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the barrier properties and related functional capabilities of nanocellulose-based layers, much research has focused on desirable attributes such as transparency Petersson and Oksman 2006;Nordqvist et al 2007;Shimazaki et al 2007;Ayuk et al 2009;Fernandes et al 2009Fernandes et al , 2010Fukuzumi et al 2009;Kim et al 2009;Nogi et al 2009;Petersson et al 2009;Sehaqui et al 2010;Hassan et al 2011;Pereda et al 2011Pereda et al , 2014Stevanic et al 2011;Yang et al 2011;Aulin et al 2012;Hu et al 2013;Li et al 2013a;Tome et al 2013;Khan et al 2014b;Kumar et al 2014;Kurihara and Isogai 2014;Tammelin and Vartiainen 2014;Ambrosio-Martin et al 2015b;Honorato et al 2015;Oun and Rhim 2015;Toivonen et al 2015a,b). Hu et al (2013) showed that nanocellulose films could be rendered conductive by deposition of tindoped indium oxide, while still retaining their transparency; solar cells prepared with such films were successfully demonstrated.…”
Section: Transparencymentioning
confidence: 99%
“…A number of researchers have demonstrated such a process when using nano-fibrillated cellulose (Nakagaito and Yano 2004Henriksson et al 2008;Nogi et al 2009;Syverud and Stenius 2009;Sehaqui et al 2010Sehaqui et al , 2011Larsson et al 2012;Hu et al 2013;Rojo et al 2015). Keshvarzi et al (2015) prepared paper-like films from a gelled mixture of nanocellulose and zeolites.…”
Section: Filtration and Papermaking Processesmentioning
confidence: 99%
“…This is comparable with the fastest preparation method reported for NFC films using a Rapid Köthen equipment. 21 They reported a total film preparation time of 1-2 h for 200 mm diameter and 45 µm thick films.…”
Section: Film Formationmentioning
confidence: 99%
“…In general the films were strong and comparable to previously reported values. 18,19,[21][22][23] However, here we note that measurements procedures, relative humidity and sample dimensions strongly influence the results and thus mechanical properties obtained in different studies should be compared with some caution. The 0.5 h pressed film has lower Young's modulus and tensile strength suggesting that indeed the pressing increases the strength of the film.…”
Section: Effect Of Applied Load On the Mechanical Properties Of Purementioning
confidence: 99%
“…Apart from application as adsorbent, CNF can also be utilized for manufacturing of nanopapers, using papermaking processes (Henriksson et al 2008;Sehaqui et al 2010;Lee et al 2012). Such nanopapers can be used as tight aqueous ultrafiltration or organic solvent nanofiltration membranes (Mautner et al 2014(Mautner et al , 2015.…”
Section: Introductionmentioning
confidence: 99%